SIGNIFIKANSI PELAYANAN PASTORAL BAGI GENERASI ALPHA PADA MASA PASCA PANDEMI - Kriswanto, Eliezer Mei (P3M STT Kristus Alfa Omega, 2023)
Restrictions on community activities including church services during the Covid-19 pandemic made the church adapt and develop new methods of carrying out pastoral service activities for the alpha generation. Likewise, ministry during the post-pandemic period also made the church further develop appropriate service strategies. This study aims to further examine the significance of pastoral care during the Covid-19 pandemic. The method used is qualitative research with literature review. The results of the study show that pastoral care for the alpha generation is significant because the method used is related to information technology.